External Prolonged Electrocardiogram Monitoring in Unexplained Syncope and Palpitations: Results of the SYNARR-Flash Study - Locati, ET (2017)
AIMS: SYNARR-Flash study (Monitoring of SYNcopes and/or sustained palpitations of suspected ARRhythmic origin) is an international, multicentre, observational, prospective trial designed to evaluate the role of external 4-week electrocardiogram (ECG) monitoring in clinical work-up of unexplained syncope and/or sustained palpitations of suspected arrhythmic origin. METHODS AND RESULTS: Consecutive patients were enrolled within 1 month after unexplained syncope or palpitations (index event) after being discharged from emergency room or hospitalization without a conclusive diagnosis. A 4-week ECG monitoring was obtained by external high-capacity loop recorder (SpiderFlash-T(®), Sorin) storing patient-activated and auto-triggered tracings. Diagnostic monitorings included (i) conclusive events with reoccurrence of syncope or palpitation with concomitant ECG recording (with/without arrhythmias) and (ii) events with asymptomatic predefined significant arrhythmias (sustained supraventricular or ventricular tachycardia, advanced atrio-ventricular block, sinus bradycardia <30 b.p.m., pauses >6 s). SYNARR-Flash study enrolled 395 patients (57.7% females, 56.9 ± 18.7 years, 28.1% with syncope, and 71.9% with palpitations) from 10 European centres. For syncope, the 4-week diagnostic yield was 24.5%, and predictors of diagnostic events were early start of recording (0-15 vs. >15 days after index event) (OR 6.2, 95% CI 1.3-29.6, P = 0.021) and previous history of supraventricular arrhythmias (OR 3.6, 95% CI 1.4-9.7, P = 0.018). For palpitations, the 4-week diagnostic yield was 71.6% and predictors of diagnostic events were history of recurrent palpitations (P < 0.001) and early start of recording (P = 0.001). CONCLUSION: The 4-week external ECG monitoring can be considered as first-line tool in the diagnostic work-up of syncope and palpitation. Early recorder use, history of supraventricular arrhythmia, and frequent previous events increased the likelihood of diagnostic events during the 4-week external ECG monitoring.